2011
DOI: 10.1002/jmv.22222
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell polyomavirus DNA in immunocompetent and immunocompromised patients with respiratory disease

Abstract: Merkel cell polyomavirus (MCPyV) was identified originally in association with a rare but aggressive skin cancer, Merkel cell carcinoma. The virus has since been found in the respiratory tract of some patients with respiratory disease. However, the role of MCPyV in the causation of respiratory disease has not been established. To determine the prevalence of MCPyV in 305 respiratory samples from immunocompetent and immunocompromised patients and evaluate their contribution to respiratory diseases, specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…It is possible that this could result in a higher sensitivity of PCR and accordingly a higher frequency of virus detection. Using primers targeting the large T-antigen gene, Abedi Kiasari et al [15] determined their PCR sensitivity to be 1,000 copies/mL. This is more than 5 times less sensitive than our VP1 PCR (<200 copies/ mL).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that this could result in a higher sensitivity of PCR and accordingly a higher frequency of virus detection. Using primers targeting the large T-antigen gene, Abedi Kiasari et al [15] determined their PCR sensitivity to be 1,000 copies/mL. This is more than 5 times less sensitive than our VP1 PCR (<200 copies/ mL).…”
Section: Discussionmentioning
confidence: 99%
“…In this group, the MCPyV prevalence rate reached 8.2%, which is higher than the results of previous studies in other countries. The frequency of detection of MCPyV DNA in NPS obtained from patients with respiratory symptoms ranges from 1.3% (Australia) to 4.2% (Sweden) [12][13][14][15]22] . It has been previously shown that the variation in MCPyV prevalence may be partially explained by methodological differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[254]- [256] A high prevalence of MCPyV was found in respiratory secretions with and without clinical symptoms suggesting it may, like other human polyomaviruses, have a respiratory route of infection. [257]- [259] Confounding studies to date are the high levels of MCPyV DNA in the environment and from skin swabs. [159], [260] MCPyV DNA is detected in 75% of environmental swabs, and can still be detected after DNAse digestion, suggesting that like HPyV6,7 & 9, MCPyV is shed as whole virions from healthy human skin.…”
Section: Human Polyomaviruses and Cancermentioning
confidence: 99%